Income and employment effects of change of roundwood use in Eastern Finland and the Republic of Karelia - Pirhonen, Ilkka; Ollonqvist, Pekka; Viitanen, Jari; Toropainen, Mikko; Bungov, Vladimir (Finnish Forest Research Institute, 2008)
Using input-output method, this study evaluates direct and indirect income and employment effects of reducing roundwood imports from Russia on both the wood working and the pulp and paper industry in Eastern Finland. Four different scenarios of roundwood import reduction and two different possibilities to increase domestic roundwood procurement were analysed. Due to lack of data, similar effects for the Republic of Karelia are calculated using two alternative scenarios to compensate reducing exports.The results indicate that forest industry, together with multiplier effects on other sectors, in Eastern Finland is facing considerable structural changes if the custom tariffs programme for roundwood exports from Russia is fulfilled. The key issue for the development of employment and incomes in Eastern Finland s forest industry is how the domestic wood procurement or roundwood imports from other countries can be increased to compensate the roundwood imports from Russia. In the worst scenario with only limited possibilities to increase domestic wood procurement, unemployment will increase nearly six thousand and value of production will decrease even by one milliard euros. Even if domestic wood procurement can compensate the reducing roundwood export amounts to some extent, the employment will decrease by few hundreds of employees and the loss in production value will be in the range of tens of thousands millions to over one hundred million euros. The only sector which will face positive income and employment effects is forestry because of increasing domestic loggings, transportation and other related services. The corresponding results for the Republic of Karelia due to the decreasing roundwood exports indicate also considerable increasing unemployment and decreasing value of output in regional economy, if the domestic production capacity especially in mechanical wood working industry is not able to increase production volumes. Vladimir Bungov was funded by Academy of Finland (grant number 121564) and Russian ...